Pengembangan Media Pop Up Book untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran PKN Kelas III di SDN 79 Pelembang - Waliya, Waliya; Arni, Yusni; Isaria, Isaria; Sunarli, Yeyen; Kadhafi, Muammar (Pusdikra-Publishing.com, 2025)
This study was conducted to produce Pop Up Book PPKN Cultural Diversity media. The purpose of this study was to determine the validity, practicality and effectiveness of the Pop-Up Book PPKN Cultural Diversity learning media for grade III at SD Negeri 79 Palembang. The type of research used was R&D (Research and Development) using the ADDIE development model (Analys, Design, Devlopment, Implementation, Evaluation). The subjects of this study were 29 grade III students at SD Negeri 79 Palembang. Meanwhile, the object of this research is the Pop Up Book PPKN Cultural Diversity learning media. The research instruments used were questionnaire sheets of material experts and media experts to determine the validity of the Pop Up Book media, student response questionnaires to determine the practicality of the Pop Up Book media, tests to measure the level of student learning success and documentation. The data analysis technique in this study used a Likert scale with an assessment score of 1-5 including data analysis of validity, practicality and effectiveness. The results of this study indicate that the Pop Up Book PPKN Cultural Diversity learning media that has been developed obtained a percentage of 90.66% with the criteria of